Sizing and Costing Optimisation of a Typical Wind/PV Hybrid Electricity Generation System for a Typical Residential Building in Urban Armidale NSW, Australia - Maklad, Yasser (International Journal of Energy Economics and Policy, 2014)
This study investigates the wind and solar electricity generation availability and potentiality for residential buildings in Armidale NSW, Australia. The main purpose of this study is to design an appropriate wind-PV hybrid system to cover the electricity consumption of typical residential buildings of various occupancy rates and relevant various average electrical daily consumption. In order to do achieve that, monthly average solar irradiance monthly average wind speed historical data observed at weather station belongs to the Australian bureau of meteorology in Armidale town over a fourteen years period from 1997–2010. Simulation of solar photovoltaic panels and wind turbines were conducted to obtain the optimal hybrid system sizing and best efficient with lowest cost. Correlations between the solar and wind power data were carried out on an hourly, daily, and monthly basis. It is shown that the hybrid system can be applied for the efficient and economic utilization of wind and solar renewable energy sources. Keywords: Hybrid system; wind energy; photovoltaic energy; Armidale NSW; renewable energy; system optimisation JEL Classifications: C1; C2; C3; C6; C9